2005
DOI: 10.1063/1.1937994
|View full text |Cite
|
Sign up to set email alerts
|

Cathodic arcs: Fractal voltage and cohesive energy rule

Abstract: The noise of the burning voltage of cathodic arcs in vacuum was analyzed for a range of cathode materials (C, Mg, Ti, V, Ni, Cu, Zr, Nb, Ag, Hf, Ta, W, Pt, Bi, and Si). Cathodic arcs were generated in a coaxial plasma source, and the voltage noise was measured with a broadband (250 MHz) measuring system. Each measurement of 50,000 points was analyzed by Fast Fourier Transform, revealing a power spectrum ~ 1/f 2 for all metals over several orders of magnitude of frequency f (brown noise). The absence of any cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 38 publications
(35 reference statements)
2
33
0
Order By: Relevance
“…The ion beam mean charge state is determined by the fraction of differently charged ions in the vacuum arc plasma. The physical aspects of the reduction of ion charge states in vacuum arc plasma were subject of our detailed investigations [4,5], which have confirmed that the reduction of ion mean charge after arc initiation is consistent with the evolution of neutrals in the volume through which the metal plasma flows. This paper considers the reduction of the ion mean charge state throughout the vacuum arc pulse from the point of view of its influence on the parameters of a vacuum arc ion source.…”
Section: Introductionmentioning
confidence: 97%
“…The ion beam mean charge state is determined by the fraction of differently charged ions in the vacuum arc plasma. The physical aspects of the reduction of ion charge states in vacuum arc plasma were subject of our detailed investigations [4,5], which have confirmed that the reduction of ion mean charge after arc initiation is consistent with the evolution of neutrals in the volume through which the metal plasma flows. This paper considers the reduction of the ion mean charge state throughout the vacuum arc pulse from the point of view of its influence on the parameters of a vacuum arc ion source.…”
Section: Introductionmentioning
confidence: 97%
“…This is generally referred to as the 'cohesive energy rule' [5]. It is related to the energy input per time and per eroded cathode material, which affects electron temperature and charge states in the plasma.…”
Section: Influence Of Cathode Compositionmentioning
confidence: 99%
“…To give a few examples: the explosive electron emission or ecton model [3]; the fractal character of several arc properties, like the burning voltage and its noise [4]; the relationship of the latter and other arc properties to the cathode material's cohesive energy [5]; or the so-called 'freezing' of ion charge state and energy distributions in the process of plasma expansion [6]. Apart from general scientific curiosity, the economic need to improve applications such as thin film and ion implantation systems and processes, as well as high current switches, is a major driving force for the advancement of the physical understanding of these phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…A short coaxial cathodic arc plasma source was flange-mounted to a cryogenically pumped vacuum chamber (it was similar to the one described in our previous work on fractal arc voltage 6 ). Most experiments were done with a planar anode (as shown in Fig.…”
Section: Experimental Setup and Measurementsmentioning
confidence: 99%